Flight activity and spread of Xylosandrus crassisuculus (Motschulsky) (Coleoptera: Curculionidae) in Brazil - Covre, Luana de Souza [UNESP]; Melo, Adriano Arrué; Flechtmann, Carlos Alberto Hector [UNESP] (Elsevier, 2021)
The granulate ambrosia beetle (GAB) Xylosandrus crassiusculus is a polyphagous species with a worldwide distribution. The species is considered a serious pest in nursery, landscape and ornamental trees, and fruit orchards. The first specimens reported for Brazil were found along the coastal region in 2012. We report here the spread inland of GAB based on ethanol-baited flight intercept trap surveys throughout the country. It is now present in regions where orchards of several fruit tree species are planted, many of them known hosts of GAB. In this article, we also provide the first information on its flight activity in a subtropical climate in South America. In Barra do Ribeiro, state of Rio Grande do Sul (southernmost state), GAB showed two flight peaks, both in the warmest months of the year, while in Rio Branco, state of Acre (northern state), there were no clear peaks; these results indicate that GAB is multivoltine in both localities. In vertical stratification studies in Tartarugalzinho, northern state of Amapá, while GAB flew at up to 8 m high, flight was concentrated at ground level.
Keywords: Ambrosia beetle; Ethanol; Flight height; Seasonality; Voltinism